Assembled design and compressive performance simulation of mine waterproof wall based on concrete 3D printing - Ren, Chuangnan; Gao, Baobin; Geng, Chenhui; Zhu, Wenjie (Frontiers in Earth Science, 2022)
With the increase of mining depth, the deep mine waterproof wall project faces the test of worse construction environment and higher risk of water damage. With the development of intelligent construction technology, it is necessary to introduce concrete 3D printing technology for the construction of coal mine waterproof walls, so as to adapt to more complex construction environment and engineering needs. Through uniaxial compression tests, the compressive properties of 3D printed concrete were tested under different printing methods and force directions. The results showed that the compressive strength of the 3D printed concrete was higher under the conditions of printing path B and loading along the direction parallel to the bonding layer. According to test results, the mine waterproof wall structure based on concrete 3D printing was designed. Then, ABAQUS was used to simulate the compressive strength and deformation of the 3D printed waterproof wall. The results showed that the ultimate load of the 3D printing module was 6.697e4kN and the deformation range was controllable, which meet the engineering requirements. The advantages of 3D printing mine waterproof walls are more flexible in design, faster in manufacturing, and more intelligent in operation. This work provides new ideas for the design and construction of waterproof walls in deep mines.